Religious Leaders as Conscience of the Nigerian Society: A Contextual Application of Matthew 14:1-5 - Oghenevwede, Tom; Ejenobo, David T. (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
alarming rate at which moral decadence is eating up the Nigerian society has become a very serious problem to social psychologists. From the craze for materialism, to an increase in ritual killings and kidnappings, youths who go by the name Yahoo Boys have polluted the moral atmosphere. Various organizations have been set up by the Government and non-governmental organizations to try to stem the tide. The results do not seem to conform to the enormity of the problem. This work posits another dimension to seeking solution to this problem. Using the encounter between King Herod and John the Baptist as narrated in Matthew 14:1-5 this work interrogates the texts to identify how religious leaders can play the function of the conscience of the society in ensuring that morality prevails in the society. Using the textual critical method of study, the hermeneutics contained in the text were identified and contextualized to the current Nigerian environment. The work identified seven distinct areas in which religious leaders in Nigeria can make their impact felt in becoming the conscience of the society. It is the contention of this work that religious leaders are most appropriately poised to lead the crusade against moral degradation in the Nigerian society. Keywords: Religious Leaders; Morality; Conscience.